Practice Patterns in Fournier's Gangrene in Europe and Implications for a Prospective Registry Study - Laila Schneidewind; Bernhard Kiss; Fabian P. Stangl; Zafer Tandogdu; Florian M. E. Wagenlehner; Truls E. Bjerklund Johansen; Béla Köves; Jose Medina-Polo; Ana Maria Tapia; Jennifer Kranz (MDPI AG, 2023)
Background: Fournier's gangrene (FG) is a life-threatening, necrotizing infection. Due to the rareness of the disease, it is challenging to plan robust prospective studies. This study aims to describe current practice patterns of FG in Europe and identify implications for planning a prospective FG registry. Methods: Online non-validated 17-items survey among urologists treating FG in in European hospitals. Questionnaires were analyzed with LimeSurvey (LimeSurvey GmbH Hamburg, Germany). Results: 229 responses from ten different European countries were submitted, and 117 (51.1%) urologists completed the questionnaire. The departments treat a mean of 4.2 (SD 3.11) patients per year. The urology department mostly takes the lead in treating FG patients (n = 113; 96.6%). The practice in FG is very heterogenic and mostly case-based all over Europe, e.g., vacuum-assisted wound closure (VAC) is mostly used (n = 50; 42.7%) as adjunct wound. The biggest challenges in FG are the short time to diagnosis and treatment, standardization and establishment of guidelines, and disease awareness. Additionally, participants stated that an international registry is an outstanding initiative, and predictive models are needed. Conclusions: There is no standard of care in the diagnosis, treatment, and long-term care of FG all over Europe. Further research could be conducted with a prospective registry.